Electrical Properties of Sr2+ and Gd3+ Codoped Ceria Electrolyte System for LT-SOFC - Koteswararao, P.; Suresh, M. Buchi; Varalaxmi, P.; Wani, B.N.; Bhaskara Rao, P.V. (Asian Journal of Chemistry, 2018)
This paper reports the effect of Sr2+ addition on electrical properties of Ce0.8Gd0.2O2-δ (GDC) electrolyte for low temperature solid oxide fuel cell application. The Sr2+ (0, 0.5, 1 and 2 mol %) doped GDC solid electrolytes have been prepared by solid state method. The sintered densities of the samples are around 95 %. Among all the compositions, the highest ionic conductivity is observed in the GDC sample with 0.5 mol % Sr addition. Nyquist plots resulted in multiple redoxation process such as grain and grain boundary conductions to the final conductivity. Estimated blocking factor is lower for the GDC electrolyte with 0.5 mol % Sr2+, indicating that Sr2+ addition promoted grain boundary conduction. Activation energies were calculated from Arrhenius plot and are found in the range of 0.80 to 1.25 eV, indicating oxygen ion conduction in the doped GDC electrolyte system of samples.